1997
DOI: 10.1016/s0896-6273(00)80318-9
|View full text |Cite
|
Sign up to set email alerts
|

TrnR2, a Novel Receptor That Mediates Neurturin and GDNF Signaling through Ret

Abstract: Glial cell line-derived neurotrophic factor (GDNF) and neurturin (NTN) comprise a family of TGF-beta-related neurotrophic factors (TRNs), which have trophic influences on a variety of neuronal populations. A receptor complex comprised of TrnR1 (GDNFR alpha) and Ret was recently identified and found to be capable of mediating both GDNF and NTN signaling. We have identified a novel receptor based on homology to TrnR1, called TrnR2, that is 48% identical to TrnR1, and is located on the short arm of chromosome 8. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
221
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 330 publications
(237 citation statements)
references
References 46 publications
15
221
1
Order By: Relevance
“…The receptor complexes include RET and various glycosylphosphatidylinositol (GPI)-anchored proteins that are required for RET dimerization; these GPI-anchored co-receptors include GFRa-1, 2, 3, and 4. 55 RET and GFRa-1 transduce a GDNF signal that plays a role in the development of the enteric nervous system and the kidney; thus, null mutations in GDNF, RET, and GFRa-1 display similar phenotypes. [56][57][58] Ligand binding to the RET complex triggers RET autophosphorylation, followed by interaction with effectors that include phospholipase Cg, Shc, Enigma, Grb2, Grb7/Grb10, Src kinase, and Ras-GAP, and resultant downstream signaling.…”
Section: Rearranged During Transfection (Ret): One Receptor Two Disementioning
confidence: 99%
“…The receptor complexes include RET and various glycosylphosphatidylinositol (GPI)-anchored proteins that are required for RET dimerization; these GPI-anchored co-receptors include GFRa-1, 2, 3, and 4. 55 RET and GFRa-1 transduce a GDNF signal that plays a role in the development of the enteric nervous system and the kidney; thus, null mutations in GDNF, RET, and GFRa-1 display similar phenotypes. [56][57][58] Ligand binding to the RET complex triggers RET autophosphorylation, followed by interaction with effectors that include phospholipase Cg, Shc, Enigma, Grb2, Grb7/Grb10, Src kinase, and Ras-GAP, and resultant downstream signaling.…”
Section: Rearranged During Transfection (Ret): One Receptor Two Disementioning
confidence: 99%
“…1a). (19)(20)(21)(22) Once the UB emerges (Fig. 1b) and begins to branch, Ret expression is downregulated in the WD and the UB trunks, and becomes restricted to the distal tips of the branches (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Gfra1 is coexpressed with Ret, consistent with its role as a co-receptor, and it can also mediate GDNF signaling independently of Ret in some circumstances. (23)(24)(25) Although Gfra1 is expressed in a slightly broader domain of the UB, and also to some extent in the mesenchyme and forming nephrons, (21,22,26) its expression in cells outside the Ret domain is entirely dispensable for normal kidney development; this was shown by targeting Gfra1 coding sequences into the Ret locus, so it was expressed in the pattern of Ret, and crossing these mice to animals lacking endogenous Gfra1. (27) The key role of GDNF and its receptors in kidney development was initially revealed by the targeted disruption of the Ret, GDNF and Gfra1 genes.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the glial cell line-derived neurotrophic factor (GDNF), neurturin (NTN) and persephin are functional ligands for the RET receptor (Durbec et al, 1996;Baloh et al, 1997;Milbrandt et al, 1998). Activation of the tyrosine kinase is mediated by glycosylphosphatidylinositol-(GPI)-anchored cell surface RET-coreceptors GDNFR-a1 ± 3 (Treanor et al, 1996;Jing et al, 1996;Baloh et al, 1997).…”
mentioning
confidence: 99%